Odpowiedzi

2009-11-25T17:06:48+01:00
A.(3x+2)do potegi2= (3x +2)² =(3x +2)(3x +2) = 9x² +12x +4
b.(2x-1)potega2-2x+4xpotega2= (2x -1)² -(2x +4x)² ?
c.(3x+1)potega2+(3x-1)potega2= (3x +1)² + (3x -1)² =
= [(3x+1)-(3x-1)]*[ (3x +1)+(3x -1)]
= [ 3x +1 -3x +1] *[ 3x +1 +3x -1]=
= [ 2]*[6x] =
= 12x

a = (3x+1)
b = (3x-1 )
a² -b² = (a -b )( a + b)


d.(2x+1)potega2-(2x-1)potega2=
= (2x+1)² - (2x -1)² =

= [(2x+1) -(2x-1)]*[ (2x +1) +(2x -1)]=
= [2x +1 -2x +1] *[ 2x+1+2x -1)]=
=[ 2]*[4x]=
= 8x


e.(61+3)potega2+36xpotega2-71xpotega2+4=

(61+3)² + 36x² -71x² +4 =
gdzieś w pierwszej części brakuje niewiadomej x
(61 +3)²